1994
DOI: 10.1080/00039896.1994.9955001
|View full text |Cite
|
Sign up to set email alerts
|

Silica Exposure and Chronic Airflow Limitation in Pottery Workers

Abstract: We assessed the relationship between exposure to silica dust and chronic airflow limitation in an epidemiological survey conducted among pottery workers and controls who were of the same socioeconomic status (average age: 35 y; 78% males). Data were collected by questionnaire for respiratory symptoms, allergy, respiratory history, smoking habits, and occupation. Lung function was measured with a computer-equipped Gauthier spirometer. We excluded subjects with silicosis or doubtful chest x-ray, and two exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 14 publications
4
11
0
2
Order By: Relevance
“…These functional changes suggested obstructive changes in airways and increased compliance. Neukirch et al 30' reported that lung function measurements, even after adjusting for age, weight and smoking habits, were significantly lower in the silica dust exposure group than in the control group, and that this was observed in both small and large airways.…”
Section: Discussionmentioning
confidence: 98%
“…These functional changes suggested obstructive changes in airways and increased compliance. Neukirch et al 30' reported that lung function measurements, even after adjusting for age, weight and smoking habits, were significantly lower in the silica dust exposure group than in the control group, and that this was observed in both small and large airways.…”
Section: Discussionmentioning
confidence: 98%
“…In other words, if we repeat this study in ten years our exposed group may show a significant drop in lung function grouping respect to controls. Lung function begins to drop at the age of 25 to 30 years, and tobacco smoke accompanied by exposure workplace reduces it further (25).…”
Section: Discussionmentioning
confidence: 99%
“…Silica exposure in diVerent workforces, such as gold miners, granite crashers, and foundry workers, has been linked to reduced spirometric lung function that seems to be independent of silicosis (Hnizdo and Vallyathan 2003). However, only a few studies have been carried out on its eVects in tile or pottery workers (Forastiere et al 2002;Neukirch et al 1994).…”
Section: Introductionmentioning
confidence: 98%